University research ethics clearances: Safety nets, or a false sense of legal immunity? - Beckmann, J. (South African Journal of Higher Education, 2017)
Ethics reviews loom large in the world of a researcher at a university. Ethics committees review research project applications meticulously and critically. They attempt to ensure that in all projects that are approved, the human respondents and participants suffer no harm that could have been prevented. However, there seems to be little acknowledgement of the possible legal repercussions of unethical research conduct. This article investigates the protection that ethics review protocols (particularly in the human sciences) offer researchers and their institutions against legal ramifications emanating from research projects where participants do suffer harm. The main finding is that research ethics protocols may offer less protection against legal implications of ethical misconduct than would generally be thought to be the case. I will make some observations on liability, vicarious liability, and the basic rights of subjects in research, after which I will offer a conclusion on the implications of this analysis for ethics reviews.